PETA PENELITIAN TERHADAP 12 JENIS BUAH LOKAL INDONESIA PADA SKRIPSI, TESIS, DAN DISERTASI LULUSAN IPB - Ratnaningsih Ratnaningsih; Deden Himawan; Abdul Rahman Saleh (Perpustakaan Nasional RI, 2017)
Fruits is generally one of the commodities needed by humans to live healthy. Although Indonesia is a large fruit-producing country, it still imports fruits from other countries, especially from the People's Republic of China. Imported fruits are often chosen by consumers because they look more attractive, the supply is guaranteed, and there are standards of quality. To produce fruits that have attractive appearance, have high production, as well as meet the quality standards it requirs quality seeds as result of long research activities on the fruits. This paper examined and mapped the results of research published in the form of bachelor thesis, thesis, and dissertation of /PB graduates. From the results of analysis, it was known that researches on 12 types of Indonesian local fruits during the last 5 years (2012-2016) were as many as 558 publications that consist of bachelor thesis as many as 417 titles, thesis as many as 117 titles, and dissertation as many as 24 titles. In bachelor thesis, the research on banana was the most conducted research that was 79 titles (18.9%) and the least was research on watermelon that was only 4 titles (1%). In thesis, the research on orange was the most conducted research that was 26 titles (22.2%) and the least was on avocado that was only 1 title (0.9%) and there was even no research on rambutan and watermelon. In dissertation, the research on mangosteen was the most conducted research that was 9 titles (37.5%) and the least research was on salak and on mango, each of which was only 1 title (4.2%). Even the doctoral program students have not conducted any research on avocado, rambutan, papaya, melon and watermelon.